Genome wide occurrence and insertion preferences of INGI/RIME and SLACS CRE transposable elements in Trypanosoma brucei. (1st November 2016) - Khan, Mohd. Faheem; Shrivastava, Kush; Sinha, Rebeka; Kumar, Virendra; Jaitly, A. K.
ABSTRACT: Retrotransposons play significant role in genome remodelling of T. brucei and about 5% of its genome consists of retrotransposons including INGI/RIME elements. INGI is one of the dispersed repetitive elements in T. brucei genome which is found distributed throughout all the chromosomes. SLACS (Spliced Leader Associated Conserved Sequence) however, is more conserved in its nature and lacks the typical poly-distributional pattern of LINE like transposons. We have found total 589 copies of these TEs with only 17.06 % (104 copies out of 589) copies with both ends intact thus showing a majority of truncated copies. Complete SLACS CRE were found only on chromosome 9, whereas, complete INGI/RIME were more ubiquitously distributed. The 50 – 70 bp upstream flanking sequence of these elements shows suitable nucleotide biophysical properties to favor transposition.